ACTUAL ISSUES OF EXECUTION OF THE EUROPEAN COURT OF HUMAN RIGHTS ACTS BY STATE ADMINISTRATION BODIES - Ilgizovna Gadelshina, Liana; Rinatovna Garifullina, Alsu; Victorovich Zheleznov, Rodion; Lenarovich Miftakhov, Renat; Albertovich Nigmetzyanov, Almaz (Revista Inclusiones, 2020)
The Purpose of this article is to identify the actual issues associated with the non-execution of decisions of the European Court of Human Rights (ECHR). The article uses a comparative analysis of the execution of ECHR acts in Russia and some member States of the Council of Europe. The main research methods are systemic and formal-legal. The authors analyzed some acts of ECHR which were not executed by Russia and the conclusions according to which the Constitutional Court of the Russian Federation recognized such acts as not possible to be executed.